2022
DOI: 10.1021/acsami.2c14909
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Tuning the Pore-Wall Surface Composition of Bioceramic Scaffolds Facilitates Angiogenesis and Orbital Bone Defect Repair

Abstract: Orbital bone damage (OBD) may result in severe post-traumatic enophthalmos, craniomaxillofacial deformities, vision loss, and intracranial infections. However, it is still a challenge to fabricate advanced biomaterials that can match the individual anatomical structure and enhance OBD repair in situ. Herein, we aimed to develop a selective surface modification strategy on bioceramic scaffolds and evaluated the effects of inorganic or organic functional coating on angiogenesis and osteogenesis, ectopically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…444 Recently, Peng et al developed a selective surface modification strategy of coating inorganic or organic components on Mg-substituted wollastonite scaffolds and evaluated the corresponding effects on angiogenesis and osteogenesis. 445 The BG coating exhibited appreciable angiogenic capability. Alternatively, a layer-by-layer coating technique involving biomimetic gels demonstrated superior intramembranous osteogenic capabilities.…”
Section: Multi-dimensional Design and Materials Science Of Silicon-co...mentioning
confidence: 99%
“…444 Recently, Peng et al developed a selective surface modification strategy of coating inorganic or organic components on Mg-substituted wollastonite scaffolds and evaluated the corresponding effects on angiogenesis and osteogenesis. 445 The BG coating exhibited appreciable angiogenic capability. Alternatively, a layer-by-layer coating technique involving biomimetic gels demonstrated superior intramembranous osteogenic capabilities.…”
Section: Multi-dimensional Design and Materials Science Of Silicon-co...mentioning
confidence: 99%
“…Bioceramics were a major kind of bulk materials. For example, Peng Y et al 45 applied two types of coating (low thermal bioglass and hyaluronic acid-chitosan biogel) on bioceramic scaffolds (CSi-Mg10) to enhance the performances of osteogenesis and angiogenesis. The results showed that both the bioglass and the biogel coatings could integrate well into the surface pore structure of the scaffolds, thus significantly enhancing their compressive strength and structural stability.…”
Section: Surface Additionmentioning
confidence: 99%
“…41 Based on these results, the 3Dprinted CSi-Mg6 scaffold alone was planted for bone defect and orbital reconstruction, and the vascularization efficacy was evaluated via μ-CT and H&E staining. 43,44 It has been found that the porous bioceramic scaffold has good structural stability, biodegradation, vascular cell migration and vascular inward growth at 4 weeks. The percentage of vessel area, vessel density and mean vessel diameter in the porous scaffold increases with time.…”
Section: Evaluation Of the Repair Effect In Minipigsmentioning
confidence: 99%